Parkinson's Disease : Molecular and Therapeutic Insights from Model Systems. - Nass, Richard (Elsevier, 2008)
Parkinsons disease is a prevalent neurodegenerative disease and is characterized by the irreversible loss of dopamine neurons. This book describes the advances and the advantages that various invertebrates, cell culture, rodents and mammals provide in the identification of the molecular components and mechanisms involved in the cell death.